Distribution of Cathepsin K in Late Stage of Tooth Germ Development and Its Function in Degrading Enamel Matrix Proteins in Mouse - Jiang, Tao; Liu, Fen; Wang, Wei-Guang; Jiang, Xin; Wen, Xuan; Hu, Kai-Jin; Xue, Yang (PloS one, 2017)
Cathepsin K (CTSK) is a member of cysteine proteinase family, and is predominantly expressed in osteoclastsfor degradationof bone matrix proteins. Given the similarity in physical properties of bone and dental mineralized tissues, including enamel, dentin and cementum, CTSK is likely to take part in mineralization process during odontogenesis. On the other hand, patients with pycnodysostosis caused by mutations of the CTSK gene displayedmultipledental abnormalities, such as hypoplasia of the enamel, obliterated pulp chambers, hypercementosis and periodontal disease. Thereforeitis necessary to study the metabolic role of CTSK in tooth matrix proteins. In this study, BALB/c mice at embryonic day 18 (E18), post-natal day 1 (P1), P5, P10 and P20 were used (5 mice at each time point)for systematic analyses of CTSK expression in the late stage of tooth germ development. We found that CTSK was abundantly expressed in the ameloblasts during secretory and maturation stages (P5 and P10) by immunohistochemistry stainings.During dentinogenesis, the staining was also intense in the mineralization stage (P5 and P10),but not detectable in the early stage of dentin formation (P1) and after tooth eruption (P20).Furthermore, through zymography and digestion test in vitro, CTSK was proved to be capable of hydrolyzing Emdogain and also cleaving Amelogenininto multiple products. Our resultsshed lights on revealing new functions of CTSK and pathogenesis of pycnodysostosis in oral tissues.